Unaccompanied minor refugees and the protection of their socio-economic rights under human rights law - Swart, Sarah Jean (University of Pretoria, 2008)
A Dissertation submitted to the Faculty of Law University of Pretoria, in partial fulfilment of the requirements for the degree Masters of Law (LLM in Human Rights and Democratisation in Africa). Prepared under the supervision of Mr E.Y. Benneh of the Faculty of Law, University of Ghana, Legon